MANAJEMEN PEMBELAJARAN DALAM MENGATASI KESULITAN BELAJAR DI MI I’ANATUL MUTA’ALLIMIN 01 KUBANGWUNGU - Dina Salamah; Triana Rosalina Noor (ICO EDUSHA, 2022)
This research is entitled “Learning Management in Overcoming at MI I’anatul Muta’allimin 01 Kubangwungu‟. Learning management has an important role in the succes and achievement of student learning. Therefore, the application of learning management can influence and provide solutions to learning difficulties experiencedc by each studcent. The formulation of the problem from this research is how to learn in overcominglearning difficulties at MI I’anatul Muta’allimin 01 Kubangwungu. The purpose of this study is to find out how the implementation of learningmanagement in overcoming learning difficulties at MI I’anatul Muta’allimin 01 Kubangwungu.This study uses a dcescriptive qualitatative approach. The research data was obtained by using observations, interview and documentation. The result of this research is that the implementation of learning management at MI I’anatul Muta’allimin 01 Kubangwungu has been going well, and has been proven to be able to overcome students learning difficulties. In planning the teacher in grade 1 determines the RPP,Prota, Promissory note, syllabus, and determination of additional material to attend a special class.organizing learning in class 1 by grouping thebbv stages of student difficulty and selecting student who will take special classes. Then the implementation of learning is carried out according to what has been planned, namely the implementation of learning in general classes and in special classes.Meanwhile, for teacher supervision by looking at student activity during the learning process, student attendance lists, student grades in the form of daily assignments, tests, semester scores, and test scores. Keywords: Learning Management, Difficulty Management, Student. References Berlian, Eri. 2016. Metodologi Penelitian Kualitatif & Kuantitatif. Padang:Sukabina Presshttps://osf.io/preprints/inarvix/aucd/. Cahyono,Hadi.2019. Faktor-faktor Kesulitan Belajar Siswa MIN Janti. Jurnal Dimensi Pendidikan dan Pembelajaran. Vol. 7, No. 1 Erma Suryani, Yulinda.2019. Kesulitan Belajar. Klaten:Magistra. Erwinsyah, Alfian. 2017.“Manajemen Pembelajaran Dalam Kaitannya Dengan Peningkatan Kualitas Guru, TADBIR: Jurnal Manajemen Pendidikan Islam, Vol.5 No.1 Gunawan,Imam.2013. Metode Penelitian Kualitatif. Jakarta:Bumi Aksara Maria, Edna dan Eko Sediyono. Pengembangan Model Manajemen Pembelajaran Berbasis TIK di Sekolah Dasar. Jurnal Manajemen Pendidikan. Vol.4.No. 1 Mukhlesi Yeni, Eti. 2015. Kesulitan Belajar Matematika Di Sekolah Dasar. Jurnal Pendidikan Nasional. Vol. 2, No. 2. Munir, Ahmad Saifulloh and Mohammad Darwis. 2020. Manajemen Pembelajaran Dalam Meningkatkan Efektivitas Proses Belajar Mengajar Di Masa Pandemi Covid-19. Bidayatuna: Jurnal Pendidikan Guru Mandrasah Ibtidaiyah 3, no. 2 Nilamsari, Natalina. 2014. Memahami Studi Dokumen Dalam Penelitian Kualitatif. Jurnal Ilmiah Ilmu Komunikasi. Vol. XIII, No. 2 Novita, Rita.dkk.2018. Penyebab Kesulitan Belajar Geometri Dimensi Tiga. Jurnal Riset Pendidikan Matematika. Vol. 1, No. 5 Sri Waskitoningtyas,Rahayu. 2016. Analisis Kesulitan Belajar Matematika Siswa Kelas V Sekolah Dasar Kota Balikpapan Pada Materi Satuan Waktu Tahun Ajaran 2015/2016.JIPM (Jurnal Ilmiah Pendidikan Matematika) 5, no. 1